PEMOGRAMAN ARDUINO TERHADAP PENINGKATAN DAYA SEPEDA MOTOR HONDA BEAT FI - Ghozali, Muhamad -; Mawardi, Iman -; Rohman, Abd (Jurnal Ilmiah Poli Rekayasa, 2023)
This study aims to obtain comparative data between the standard Honda BeAT PGM-FI motorbikes and those added by Arduino with an interpolated model. Interpolation is a method for obtaining data based on some known data. The method used is experimental based on relevant references. From the test results, it was found that the standard condition data was 6.2 hp at 2500 and 2655 rpm. while with the addition of Arduino the power value is 6.3 hp at 2500, 2664 and 2750 rpm. So that there is an increase in power of 0.1 hp or 1.58% between standard conditions and those using Arduino interpolation patterns.